IMPORTANCE OF MODERN TECHNOLOGIES IN NATURE PROTECTION (British Journal of Global Ecology and Sustainable Development, 2024)
In the article, innovations and modern technologies show their impact on various areas of our life, including the ease of the work of experts in the field of nature conservation and protection, as well as the transparent development of the field. Technology has become an integral part of the industry and has fundamentally changed the way we work. Through these technologies, the issues of ecological legal responsibility, creating an opportunity to closely study representatives of the animal world were discussed.